2017
DOI: 10.3390/ma10060612
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Stable Ionic-Type Hybrid Gate Dielectrics for High Mobility Solution-Processed Metal-Oxide Thin-Film Transistors

Abstract: In this paper, we demonstrate high mobility solution-processed metal-oxide thin-film transistors (TFTs) by using a high-frequency-stable ionic-type hybrid gate dielectric (HGD). The HGD gate dielectric, a blend of sol-gel aluminum oxide (AlOx) and poly(4-vinylphenol) (PVP), exhibited high dielectric constant (ε~8.15) and high-frequency-stable characteristics (1 MHz). Using the ionic-type HGD as a gate dielectric layer, an minimal electron-double-layer (EDL) can be formed at the gate dielectric/InOx interface, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…The EDL capacitor is formed by electrostatic accumulation, whereas the pseudo‐capacitor is formed by the Faradaic charge‐transfer process, which is an electrochemical process (Figure d) . With these materials as capacitors, the C ‐ f diagram can be displayed in three cases (Figure e): 1) a normal dielectric only containing bulk capacitance (bottom); 2) an electrolyte‐like dielectric containing EDL capacitance and bulk capacitance (middle); 3) an electrolyte‐like dielectric layer containing pseudocapacitance, EDL capacitance and bulk capacitance (top) . In particular, oxide materials (e.g., SiO x and AlO x ) fabricated by the solution method can be called ionic conductors or solid‐state electrolytes, which is defined as a solid material conducting mainly by ionic migration but acting as an insulator for electrons .…”
Section: Ideal and Nonideal Ofetsmentioning
confidence: 99%
“…The EDL capacitor is formed by electrostatic accumulation, whereas the pseudo‐capacitor is formed by the Faradaic charge‐transfer process, which is an electrochemical process (Figure d) . With these materials as capacitors, the C ‐ f diagram can be displayed in three cases (Figure e): 1) a normal dielectric only containing bulk capacitance (bottom); 2) an electrolyte‐like dielectric containing EDL capacitance and bulk capacitance (middle); 3) an electrolyte‐like dielectric layer containing pseudocapacitance, EDL capacitance and bulk capacitance (top) . In particular, oxide materials (e.g., SiO x and AlO x ) fabricated by the solution method can be called ionic conductors or solid‐state electrolytes, which is defined as a solid material conducting mainly by ionic migration but acting as an insulator for electrons .…”
Section: Ideal and Nonideal Ofetsmentioning
confidence: 99%
“…It is acknowledged that electrical double layer formed in the solution-processed metal oxide gate dielectrics will lead to higher capacitance [41,42], as shown in the inset of Fig. 6b.…”
Section: Thin Film and Device Characterizationmentioning
confidence: 99%
“…13 Heo et al attributed the mobility enhancement to electric double layer (EDL) formation at the solutionprocessed AlO x /InO x interface. 14 In most cases, large capacitance induced by EDL can lead to low operating voltage. However, numerical simulations have revealed that, once the…”
mentioning
confidence: 99%
“…The strong dependence of capacitance on frequency and voltage suggests the possible formation of pseudocapacitance in addition to the EDL. 19 Usually, solution-processed gate dielectrics fabricated at low temperatures are not dense and feature unintentional defects causing cations and anions, 14 which can be regarded as solid-state electrolytes. 20−22 With the EDL effect, charge accumulation is achieved electrostatically at the gate/electrolyte and electrolyte/semiconductor interfaces, and the EDL capacitance C EDL arises from the surface-charge density.…”
mentioning
confidence: 99%
See 1 more Smart Citation